Discrete evolutionary particle swarm optimization for multiyear transmission expansion planning - Manuel Costeira da Rocha (2011)
This paper presents a discrete approach, based on an improved integer version of the evolutionary particle swarm optimization (EPSO) algorithm, to solve the dynamic transmission expansion planning (TEP) problem. TEP corre-sponds to a mixed integer optimization problem that typically aims at identifying a schedule for transmission additions along an extended planning horizon considering operation and investment costs as well as a reliability index to measure the ability the system has to convey electricity from genera-tion to consumers. After detailing the mathematical formula-tion of the TEP problem, this paper describes the enhanced EPSO algorithm and details its application to the TEP prob-lem. The paper also includes a Case Study based on the IEEE 24 bus / 38 branch system to illustrate the application of the developed procedure.